2015
DOI: 10.1038/srep13413
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale RNA-Seq Transcriptome Analysis of 4043 Cancers and 548 Normal Tissue Controls across 12 TCGA Cancer Types

Abstract: The Cancer Genome Atlas (TCGA) has accrued RNA-Seq-based transcriptome data for more than 4000 cancer tissue samples across 12 cancer types, translating these data into biological insights remains a major challenge. We analyzed and compared the transcriptomes of 4043 cancer and 548 normal tissue samples from 21 TCGA cancer types, and created a comprehensive catalog of gene expression alterations for each cancer type. By clustering genes into co-regulated gene sets, we identified seven cross-cancer gene signatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
88
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(93 citation statements)
references
References 175 publications
4
88
1
Order By: Relevance
“…Using systems biology approaches, others successfully clarified the role of small molecular decision circuits (e.g., Faratian et al, 2009; Gaglio et al, 2011; Tyson et al, 2011) and found commonalities across different cancers through pan-cancer analyses (e.g., Weinstein et al, 2013; Zack et al, 2013; Leiserson et al, 2014; Aran et al, 2015; Peng et al, 2015). However, few studies have addressed ROS metabolism using systems approaches (Zhang et al, 2010; Zhou et al, 2011; Zhan et al, 2012).…”
Section: Systems Biology and Personalized Medicine Approaches Are Funmentioning
confidence: 99%
“…Using systems biology approaches, others successfully clarified the role of small molecular decision circuits (e.g., Faratian et al, 2009; Gaglio et al, 2011; Tyson et al, 2011) and found commonalities across different cancers through pan-cancer analyses (e.g., Weinstein et al, 2013; Zack et al, 2013; Leiserson et al, 2014; Aran et al, 2015; Peng et al, 2015). However, few studies have addressed ROS metabolism using systems approaches (Zhang et al, 2010; Zhou et al, 2011; Zhan et al, 2012).…”
Section: Systems Biology and Personalized Medicine Approaches Are Funmentioning
confidence: 99%
“…From a clinical perspective, HTS has great potential in the development of cancer diagnostics (Peng et al, 2015), the identification of disease-relevant genetic variations (Renkema et al, 2014;Liu et al, 2015), and clinical applications for regenerative therapy and personalized medicine (Casanova et al, 2014;Cox et al, 2015). In particular, the applications of HTS have been used to characterize the human oral microbiome, one of the most diverse microbial communities that is increasingly important for studying human oral cancers and pathogens (Xu and Gunsolley, 2014;Duran-Pinedo and Frias-Lopez, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Compared with traditional DNA sequencing technology, RNA sequencing can help understand the transcriptome via precisely and rapidly deriving wide-range strand information, such as transcripts, isoforms, gene fusions, and non-coding RNAs (Wang et al, 2009). The TCGA data that is generated by the RNASeq platform provides researchers with standardized and comprehensive cancer transcriptome profiles to discover biomarkers related to tumorigenesis and metastasis (Peng et al, 2015).…”
Section: Tcga Cancer Type and High-throughput Platform Generated Datamentioning
confidence: 99%